SAFETY ISSUES IN THE TREATMENT OF PATIENTS TAKING DABIGATRAN - E. S. Kropacheva («REMEDIUM GROUP» Ltd., 2016)
In a question-and-answer format, the most critical issues concerning the safety of therapy and management  of patients taking dabigatran are considered in the article. Particular attention is paid to the prospects of anticoagulant therapy in patients with comorbidities, as well as interactions between novel oral anticoagulants  and other groups of medications, risk assessment of potential complications of therapy.